Anti-SARS-CoV-2 and anticoagulant properties of Pentacta pygmaea fucosylated chondroitin sulfate depend on high molecular weight structures. (22nd September 2022) - Dwivedi, Rohini; Sharma, Poonam; Eilts, Friederike; Zhang, Fuming; Linhardt, Robert J; Tandon, Ritesh; Pomin, Vitor H
Abstract: Fucosylated chondroitin sulfate (FucCS) is a unique marine glycosaminoglycan that exhibits diverse biological functions, including antiviral and anticoagulant activity. In previous work, the FucCS derived from Pentacta pygmaea (PpFucCS) showed moderate anticoagulant effect but high inhibitory activity against the Wuhan strain of severe acute respiratory syndrome coronavirus (SARS-CoV-2). In this study, we perform free-radical depolymerization of PpFucCS by the copper-based Fenton method to generate low molecular weight (MW) oligosaccharides. PpFucCS oligosaccharides were structurally analyzed by 1 H nuclear magnetic resonance spectroscopy and were used to conduct structure–activity relationship studies regarding their effects against SARS-CoV-2 and clotting. Anticoagulant properties were measured by activated partial thromboplastin time, protease (factors Xa and IIa) inhibition by serine protease inhibitors (antithrombin [AT] and heparin cofactor II [HCII]), and competitive surface plasmon resonance (SPR) assay using AT, HCII, and IIa. Anti-SARS-CoV-2 properties were measured by the concentration-response inhibitory curves of HEK-293T-human angiotensin-converting enzyme-2 cells infected with a baculovirus pseudotyped SARS-CoV-2 Delta variant spike (S)-protein and competitive SPR assays using multiple S-proteins (Wuhan, N501Y [Alpha], K417T/E484K/N501Y [Gamma], L542R [Delta], and Omicron [BA.2 subvariant]). Cytotoxicity of native PpFucCS and oligosaccharides was also assessed. The PpFucCS-derived oligosaccharide fraction of the highest MW showed great anti-SARS-CoV-2 Delta activity and reduced anticoagulant properties. Results have indicated no cytotoxicity and MW dependency on both anti-SARS-CoV-2 and anticoagulant effects of PpFucCS, as both actions were reduced accordingly to the MW decrease of PpFucCS. Our results demonstrate that the high-MW structures of PpFucCS is a key structural element to achieve the maximal anti-SARS-CoV-2 and anticoagulant effects.